Workplace Well Being dan Psychology Capital Pada Pegawai Perusahaan Umum Daerah Air Minum Tirta Khatulistiwa di Pontianak - Maharani, Tiara; V, Vidyastuti; Lestari, Widya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to explore the relationship between workplace well-being and psychological capital at the Perumda Air Minum Tirta Khatulistiwa Pontianak. Utilizing a quantitative approach with a sample of 136 employees, the research assessed psychological capital through dimensions of self-efficacy, optimism, hope, and resiliency, and workplace well-being through core effect and work value dimensions. The findings reveal a significant positive relationship between the two variables, with a correlation coefficient (R) of 0.790 and a significance level (p-value) of 0.000, indicating that higher psychological capital contributes to increased workplace well-being and vice versa. Simple linear regression analysis shows that workplace well-being accounts for 62.4% of the variance in psychological capital, with the remaining 37.6% influenced by other variables such as emotional intelligence. The study also indicates that employees with high psychological capital experience better workplace well-being, reflected in higher satisfaction, motivation, and productivity. Conversely, employees with lower psychological capital face challenges in managing stress and workplace demands. These findings emphasize the importance of organizational support in developing psychological capital and creating a supportive work environment to enhance employee performance and well-being. The study suggests that organizations should focus on fostering psychological capital and providing a positive work environment to achieve better organizational outcomes.